Women in antiquity: real women across the ancient world - Budin, Stephanie Lynn; Turfa, Jean MacIntosh (Rewriting antiquity, 2016)
pt. 1. Mesopotamia -- pt. 2. Egypt -- pt. 3. Hittites -- pt. 4. Cyprus -- pt. 5. The Levant and Carthage -- pt. 6. The Aegean, Bronze Age and historical -- pt. 7. Etruria and the Italian archipelago -- pt. 8. Rome -- pt. 9. At the edges -- pt. 10. Coda.